Better Attitudes toward Cybersecurity and Greater Self-Control Predict Lower Risky Online Behaviors among Nurses - Othman, Elham H.; Haj, Wasem I. AL; Alosta, Mohammad R.; Qan'Ir, Yousef; Aburuz, Mohannad Eid; Almagharbeh, Wesam Taher (Applied Clinical Informatics, 2025)
The current study examined the moderating effect of self-control on the relationship between attitudes toward cybersecurity and risky online behaviors among direct care nurses.A cross-sectional study collected data from 260 direct care nurses in Saudi Arabia using a self-reported questionnaire. Hierarchical multiple regression analysis and simple slope analysis examined the moderation effect of self-control on the relationship between attitudes toward cybersecurity and risky online behaviors.We found that a better attitude toward cybersecurity and greater self-control predicted lower risky online behaviors. Simple slope tests revealed a significant negative association between attitude toward cybersecurity and risky online behaviors at low levels of self-control, but this association disappears at high levels of self-control, meaning that high levels of self-control have a protective/moderating effect on the relationship between attitude toward cybersecurity and risky online behaviors.Self-control moderates the effect of attitudes on online practices. The negative attitudes' influence on risky online behaviors is stronger when self-control is low. On the other hand, at high levels of self-control, individuals may engage in safer practices regardless of their attitudes.
Keywords: cybersecurity attitude; cybersecurity training; electronic health record; electronic medical record; health care data; risky cybersecurity behaviors; self-control; moderation effect